Anti-fungal medication and sarcoidosis - Terčelj-Zorman, Marjeta (Zdravniški vestnik, 2010)
Background: Previous studies on sarcoidosis have shown that the addition of ananti-fungal medication to the traditional treatment with corticosteroids improves treatment efficiency. It cannot be excluded that the effect is due toa stimulatory effect of the anti-fungal medication on the action of corticosteroids. To assess this possibility a study was undertaken where patients with sarcoidosis stage 2 were given an antifungal medication only. Material and methods: Study subjects (n=10) were recruited from newly diagnosed cases of sarcoidosis and observed for 3 months to reduce the risk ofincluding patients with spontaneous regression of the disease. They were given an anti-fungal medication for 2-11 months and x-rays were taken before and every second month after starting the treatment. Diffusion capacity, serumangiotensin converting enzyme, and chitotriosidase were determined as markers of sarcoidosis activity. Results: There were improvements in the x-rayfindings as well as the markers of sarcoidosis in 8 out of 10 patients. Two patients had an exacerbation of their disease after two months and they were given corticosteroids in addition to the anti-fungal medication. Comments: The results demonstrate that the beneficial effects of anti-fungal medication are specific and not caused by an improvement of corticosteroid efficacy. The findings provide a basis for larger clinical studies.
Keywords: Antifungal Agents; Antimikotiki; Drug Therapy; Sarcoidosis; Sarkoidoza; therapy; Treatment Outcome; zdravljenje; Zdravljenje, izid